Manajemen Sumber Daya Manusia dalam Peningkatan Mutu Pendidikan di MTs Al Khairiyah Kaliawi Bandar Lampung - Nurul Istiqomah; Siti Patimah; Fisman Bedi; Sovia Mas Ayu; Junaidah Junaidah (STKIP Pesisir Selatan, 2024)
Human resources are the most important asset in an organization/company, especially in an educational institution, so it is very important that existing human resources can be planned as well as possible, for the realization of organizational/institutional goals. The purpose of writing is to find and examine more deeply about human resource management in improving the quality of education at MTs Al Khairiyah Kaliawi Bandar Lampung. The method of writing this scientific article uses a qualitative method. Data is obtained through observation, where the researcher functions as an instrument to make observations, in-depth interviews with primary data sources and study documentation. The data were analyzed with interactive analysis through 3 activities, namely data reduction, data presentation, and conclusion drawing. The results of this study are HR planning is designed and arranged systematically and based on school independence by taking into account the characteristics of the school, HR recruitment is carried out by prioritizing the principles of professionalism, selection is judged to have fulfilled professional elements, training conducted has had a positive impact and influence both for schools and personnel, work appraisal is carried out using two aspects, namely quantitative and qualitative aspects, compensation.